The use of circulating biomarkers in early clinical trials in patients with cancer. (October 2015) - D'Arcangelo, Manolo; Margetts, Jane; Greystoke, Alastair
The development of targeted therapies has changed the approach to early oncological clinical trial design. Identification of patient populations most likely to derive benefit and the biologically effective dose are now as important as determination of the maximum tolerated dose. Completion of the 'pharmacological audit trail' highlights drugs most likely to progress through to license, so resources can be allocated appropriately. Key to the success of this changing model is the validation/qualification of circulating biomarkers. These might provide a readily accessible and dynamic picture of drug effect, tumor response and toxicity with minimum risk to patients. This review article examines circulating biomarkers currently used in early oncological clinical trials. It considers the evidence for their employment, limitations and challenges for future development.